Systematic Analysis of bHLH Transcription Factors in Cassava Uncovers Their Roles in Postharvest Physiological Deterioration and Cyanogenic Glycosides Biosynthesis - An, Feifei; Xiao, Xinhui; Chen, Ting; Xue, Jingjing; Luo, Xiuqin; Ou, Wenjun; Li, Kaimian; Cai, Jie; Chen, Songbi (Frontiers in Plant Science, 2022)
The basic helix-loop-helix (bHLH) proteins are a large superfamily of transcription factors, and play a central role in a wide range of metabolic, physiological, and developmental processes in higher organisms. However, systematic investigation of bHLH gene family in cassava (Manihot esculenta Crantz) has not been reported. In the present study, we performed a genome-wide survey and identified 148 MebHLHs genes were unevenly harbored in 18 chromosomes. Through phylogenetic analyses along with Arabidopsis counterparts, these MebHLHs genes were divided into 19 groups, and each gene contains a similar structure and conserved motifs. 7 duplicated gene pairs were identified, and almost exhibited strong purifying selection during evolution. In addition, various cis-acting regulatory elements in MebHLH genes were related to major defense and stress responses. Notably, transcriptome data analyses unveiled the expression profiles of 117 MebHLH genes under postharvest physiological deterioration (PPD) of cassava tuberous roots, while 65 MebHLH genes showed significantly change. Furthermore, the expression profiles of 15 MebHLH genes tested by quantitative real-time PCR demonstrated that they were sensitive to PPD, suggesting they may involve in PPD process regulation. Cyanogenic glucosides biosynthesis during PPD process was increased, silencing of MebHLH72 and MebHLH114 showed that linamarin content was significantly decreased in the leaves. Taken together, the genome-wide identification and expression profiling pave new avenues for systematic functional analysis of MebHLH candidates, which will accelerate the improvement of PPD tolerance and decrease cyanogenic glucosides content in cassava tuberous roots.